Disagreement Strategies of Madurese Senior High School and College Graduates - Kristiyanti, Rahma; Ratnadewi, Dwijani; Wijaya, Armeria (New Language Dimensions, 2022)
Research on disagreement is always associated with politeness. Research on politeness strategies for native local language outside the actual location has not much observed. This research aims to identify the disagreement strategies in Indonesian used by Senior High School (SHS) and College (C) graduates of Madurese who have lived in Surabaya for more than five years. This study used a survey design (quantitative method) by applying a questionnaire and interview as the instruments. The subjects of this research were 25 SHS graduates and 25 C graduates. To analyze the data, SPSS version 2.0 was used. The results of data analysis showed that Madurese SHS and C graduates chose the disagreement strategy of expression of regret, contradiction, hedges opinion, counterclaims and token agreement. The expression of regret and counterclaims strategy served as the dominant strategies mostly expressed with the reason that they were common, easy and the most suitable strategy for disagreeing.